Instantaneous deposition-rate modulator for vacuum vapor deposition: fabrication of polarization gradated organic film - Sowon Kim; Masahiro Ohara; Hirohiko Fukagawa; Hisao Ishii (Applied Physics Express)
The molecular orientation and properties of vapor-deposited organic films are essential for device performance and typically governed by the deposition rate. Controlling the orientation during film growth allows the optimization of local properties from the interface to the bulk region. However, conventional deposition faces challenges in rapid wide-ranging rate adjustment due to the required stabilization time. We introduce a velocity selector that enables instantaneous deposition rate changes by modulating the molecular transmission through blade rotation. Using the proposed selector, we precisely control the spontaneous orientation polarization in Alq _3 films by continuously varying deposition rates, achieving flexible polarization grading within organic films.